2020
DOI: 10.1080/13683500.2020.1776687
|View full text |Cite
|
Sign up to set email alerts
|

Perceived authenticity of traditional branded restaurants (China): impacts on perceived quality, perceived value, and behavioural intentions

Abstract: This study attempts to investigate the perceived authenticity of consumers in Chinese traditional branded restaurants, as well as to investigate the specific factors that contribute to consumers' perceived authenticity. It constructs a systematic model addressing whether, and how, consumers' perceived authenticity, can influence their behavioural intentions through perceived quality of food, service, and dining environment, as well as perceived values in traditional branded restaurants. Results were derived fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 70 publications
4
52
0
1
Order By: Relevance
“…Some studies in the broader tourism context reported that perceived value influences loyalty [31,43,49]. This study examines the relationship between perceived value and loyalty in the context of marine tourism.…”
Section: Perceived Value and Loyaltymentioning
confidence: 97%
See 4 more Smart Citations
“…Some studies in the broader tourism context reported that perceived value influences loyalty [31,43,49]. This study examines the relationship between perceived value and loyalty in the context of marine tourism.…”
Section: Perceived Value and Loyaltymentioning
confidence: 97%
“…Studies suggested that tourists' perception of authenticity is based on tangible and intangible factors. The former includes exterior features and interior decoration of buildings, as well as surrounding environment and ambience in tourism attractions/destinations [28][29][30][31]. The intangible factors are mainly customs and traditions, such as clothing, food, art, stories, festivals and cultural rituals.…”
Section: Object-based Authenticity and Existential Authenticity In Tomentioning
confidence: 99%
See 3 more Smart Citations